1996
DOI: 10.1074/jbc.271.19.11047
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A Confers Structure-specific Endonuclease Activities to the XPF-ERCC1 and XPG Subunits of Human DNA Repair Excision Nuclease

Abstract: XPF-ERCC1 and XPG proteins are nucleases that are involved in human nucleotide excision repair. In this study, we characterized the structure-specific junctioncutting activities of both nucleases using DNA substrates containing a bubble or loop structure. We found that the junction-cutting activities of XPF-ERCC1 and XPG were greatly stimulated by human replication protein A (RPA), while heterologous single-stranded DNAbinding proteins could not substitute for human RPA. To test for specific interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 27 publications
6
153
0
Order By: Relevance
“…RPA is a well‐established XPF‐interacting factor, required to position and activate XPF‐ERCC1 for incisions made 5′ to the lesion during nucleotide excision repair (Matsunaga et al , 1996; Bessho et al , 1997; de Laat et al , 1998b). To explore the effect of RPA on XPF‐ERCC1 activity, a simple fork substrate was pre‐incubated with increasing concentrations of recombinant human RPA on ice for 10 min prior to reaction with 40 nM XPF‐ERCC1 for 60 min at 30°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RPA is a well‐established XPF‐interacting factor, required to position and activate XPF‐ERCC1 for incisions made 5′ to the lesion during nucleotide excision repair (Matsunaga et al , 1996; Bessho et al , 1997; de Laat et al , 1998b). To explore the effect of RPA on XPF‐ERCC1 activity, a simple fork substrate was pre‐incubated with increasing concentrations of recombinant human RPA on ice for 10 min prior to reaction with 40 nM XPF‐ERCC1 for 60 min at 30°C.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we determined whether any known XPF‐ERCC1‐interacting factors relevant to replication‐coupled ICL repair could modulate this reaction. Consequently, we investigated a very well‐established XPF‐ERCC1‐interacting partner relevant to replication‐coupled repair, RPA (Matsunaga et al , 1996; Bessho et al , 1997; de Laat et al , 1998b). Strikingly, for simple fork structures RPA was able to dramatically stimulate XPF‐ERCC1 cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The T [6 -4]T photoproduct containing substrate was constructed by ligating the damage-containing oligomer (8-mer), which was 5Ј-terminally labeled, with other partially overlapping oligonucleotides to obtain the internally labeled duplex as described (19,20). The resulting 46-bp duplex contains the (6-4) photoproduct at positions 23 and 24.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of these complexes may be promoted by the strand separation activity of RPA (22). In addition, RPA participates in the dual incision by stimulating the XPF-ERCC1 endonuclease (23)(24)(25). Lastly, RPA has been implicated in the coordination of DNA synthesis after removal of DNA lesions (26).…”
Section: Replication Protein a (Rpa)mentioning
confidence: 99%
“…We previously found that RPA highly stimulates the structure-specific endonuclease activity of XPF-ERCC1 using a 32 P-labeled substrate containing a stretch of 30 unpaired nucleotides (23,24). This bubble struc- ture mimics the unwound state of DNA generated around the lesion by the helicase activity of the excision repair factor TFIIH (12,49).…”
Section: Rpa4 Mrna Is Found In Normal Humanmentioning
confidence: 99%